Establishing the patterns in anode behavior of copper in phosphoric acid solutions when adding alcohols - Silchenko, Dar’ja; Pilipenko, Alexei; Pancheva, Hanna; Khrystych, Olena; Chyrkina, Marina; Semenov, Evgeny (Eastern-European Journal of Enterprise Technologies, 2018)
We have investigated the anodic polarization dependences of the copper electrode in phosphate-alcoholic solutions. The dependences derived can be divided into regions, each of which corresponds to the course of certain electrochemical reactions within the specified range of potentials. The first region corresponds to the anodic dissolution of copper, the second region ‒ to the formation at the surface of copper of a passivating oxide-salt film and the diffusion regime of metal dissolution. Upon reaching the potential for the decomposition of water, the dissolution of a copper electrode is accompanied by the oxidation of Н2О molecules. We have established the relationship between patterns of copper dissolution and polarization dependences of the electrode. Electrochemical etching of copper is matched with the range of electrode potentials of 0‒0.8 V. Formation of an oxide-salt film at potentials of 1‒2 V predetermines the ionization of copper under diffusion mode and leads to the preferential dissolution of metal’s micro-irregularities with the formation of the shiny surface of the electrode. Shifting the anode potential towards magnitudes exceeding 2 V leads to the emergence of point etching at the surface of copper because of a local disruption in the continuity of a passive film. Adding ethanol to the solutions of phosphoric acid reduces current density of the anodic copper dissolution in the stationary area to the values of 0.2‒2 A∙dm–2. Ethanol helps obtain a shiny surface of copper. At (С2Н5ОН)>30 %, the polishing effect disappears. Butyl alcohol is an effective inhibitor of copper etching and in its presence ja reduces to 0.1‒1 A∙dm–2. Adding C4H9OН predetermines the formation of surface with a strong gloss and the minimum number of etching points. At (с(C4H9OН)>50 %, copper surface acquires a significant number of etching points. Inhibitory effect of glycerol is close to the action of butanol. The shape of the polarization dependence is predetermined by the C3H8O3 content in solution. When increasing с(C3H8O3)>20 %, polishing does not occur and the surface of the electrode has a matte appearance. The data obtained show that the anodic behavior of copper depends on the nature of an additive, which could be used to develop the polishing electrolytes or the dimensional copper treatment.